What’s your pronoun? Reflections on gender issues in European languages - Maturi, Pietro (Fuori Luogo Journal of Sociology of Territory, Tourism, Technology, 2021)
The social, political and cultural developments which brought during the last few decades to a change in the relationships between gender find an important correlate in linguistic usage, which on the one hand reflects changes and on the other sustains and strengthens it. Such new usages affect in particular, in many European languages, the correct use of the feminine gender when defining a woman’s profession or social role. Italian seems to be late in accepting the change (Avvocata? Avvocatessa? Donna avvocato? Avvocato donna?), whereas French, German and Spanish don’t hesitate in using the feminine (avocate/Anwältin/abogada). English, on the other hand, where no such gender distinction holds for the vast majority of nouns, is moving in the opposite direction, abolishing the few cases formerly existing (no longer actor vs. actress but actor or performer for all). One specially sensitive and interesting case are the pronouns: if all languages use the pronoun corresponding to the person’s gender, what happens when we don’t know the gender of a particular person? Some languages have been developing new forms of genderless pronoun in order to avoid repetitions: in English each student must bring his/her own book has been replaced by each student must bring their book; in Swedish han/hon (he/she) gave way to hen for everyone. Such genderless forms, by the way, are also used by non binary and gender fluid people in order to avoid the choice between masculine and feminine. Finally, the attempt not to repeat masculine and feminine forms in addressing groups (it. Cari colleghi e care colleghe, and so on) led to the research for new graphic solutions, such as, in Italian, the asterisk (car* collegh*) or, more recently the IPA symbol for schwa (car« collegh«).